Implementation and Operational Research: Engagement in HIV Care Among Persons Enrolled in a Clinical HIV Cohort in Ontario, Canada, 2001–2011. (1st September 2015) - Burchell, Ann N.; Gardner, Sandra; Light, Lucia; Ellis, Brooke M.; Antoniou, Tony; Bacon, Jean; Benoit, Anita; Cooper, Curtis; Kendall, Claire; Loutfy, Mona; McGee, Frank; Raboud, Janet; et al.
Abstract : Background: Ensuring that people living with HIV are accessing and staying in care is vital to achieving optimal health outcomes including antiretroviral therapy (ART) success. We sought to characterize engagement in HIV care among participants of a large clinical cohort in Ontario, Canada, from 2001 to 2011. Methods: The Ontario HIV Treatment Network Cohort Study (OCS) is a multisite HIV clinical cohort, which conducts record linkage with the provincial public health laboratory for viral load tests. We estimated the annual proportion meeting criteria for being in care (≥1 viral load per year), in continuous care (≥2 viral load per year ≥90 days apart), on ART, and with suppressed viral load <200 copies per milliliter. Ratios of proportions according to socio-demographic and clinical characteristics were examined using multivariable generalized estimating equations with a log-link. Results: A total of 5380 participants were followed over 44, 680 person-years. From 2001 to 2011, we observed high and constant proportions of patients in HIV care (86.3%–88.8%) and in continuous care (76.4%–79.5%). There were statistically significant rises over time in the proportions on ART and with suppressed viral load; by 2011, a majority of patients were on ART (77.3%) and had viral suppression (76.2%). There was minimal variation in HIV engagement indicators by socio-demographic and HIV risk characteristics. Conclusions: In a setting with universal health care, we observed high proportions of HIV care engagement over time and an increased proportion of patients attaining successful virologic suppression, likely due to improvements in ART regimens and changing guidelines. Abstract : Supplemental Digital Content is Available in the Text.